High velocity impact response and damage analysis of hybrid aluminum/carbon fiber/pineapple leaf fiber laminates for automotive structure using TOPSIS method - Xiao, Hanyue; Hameed Sultan, Mohamed Thariq; Shahar, Farah Syazwani; Nayak, Suhas Yeshwant; Najeeb, Muhammad Imran; Muhammad Amir, Siti Madiha; Rahim, Sapizah (Taylor and Francis, 2025)
With the rising demand for lightweight and high-performance materials in automotive applications, this study examines the high-velocity impact (HVI) behavior and damage mechanisms of fiber metal laminates (FMLs) composed of aluminum (A), carbon fiber (C), and pineapple leaf fiber (P). Using the Technique for Order Preference by Similarity to the Ideal Solution (TOPSIS), we identified the optimal FMLs from four layer sequences (APPPA, ACPCA, APCPA, and CPAPC). The best-performing FML, ACPCA, was tested at various impact velocities (73.33 m/s, 86.08 m/s, 92.33 m/s, 101.35 m/s, 132.96 m/s, and 144.27 m/s). Damage modes and failure were analyzed through visual inspection, infrared thermography (IR), radiography testing (RT), and scanning electron microscopy (SEM). Results showed that the ACPCA specimen absorbed all impact energy up to 92.33 m/s without complete perforation but was fully penetrated at higher velocities. The highest energy absorption recorded was 29.74 J at 132.96 m/s, with a specific energy absorption (SEA) of 76.49%. Given their exceptional energy absorption capabilities, hybrid FMLs demonstrate excellent potential for automotive applications, such as door panels, roof structures, bumpers, and vehicle armor, where impact resistance, durability, and lightweight properties are critically important.